Alfalfa Cost-Return Budget in South Central and Southeast Kansas - Fausett, Marvin R.; Warmann, Gerald W. (My University, 1998)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa production in south central and southeast Kansas.
MF363_1998_10
Keywords: MF363; Economics; Crops; MF